If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 + 7x) = 12 (2 * 6 + 7x * 6) = 12 (12 + 42x) = 12 Add '-12' to each side of the equation. 12 + -12 + 42x = 12 + -12 Combine like terms: 12 + -12 = 0 0 + 42x = 12 + -12 42x = 12 + -12 Combine like terms: 12 + -12 = 0 42x = 0 Solving 42x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '42'. x = 0 Simplifying x = 0
| 3x+9y=-108 | | 8n+13=7(n+10) | | 8x-9=4x | | 3(2X+2)-4(3X+2)=5X+20 | | (6x-3)=(4x+7) | | 2x=(360+2) | | (6)*(3x+2)=(6)*(5x-10) | | R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x |